¿Dictar o enseñar? : la experiencia de Academia : Revista sobre la enseñanza del Derecho en la constitución de un espacio de reflexión sobre la práctica docente en la UBA - Beloff, Mary (2011)
This paper aims at analyzing the role law journals play it for the reflection on models of legal education, teaching strategies and teaching practices in the context of processes of change of curriculum. In particular we analyze the case of Academy. Revista sobre enseñanza del Derecho published by the University of Buenos Aires.